Beyond XML firewalling security coordination for web services. - Boubez, Toufic (SOA webservices journal.)
Traditional development produces applications that are closed to wide usage. Custom development is required to open these programs to wide-scale integration. In contrast, Web services applications are by default open to other systems and additional configuration is required to block access.